Kronecker Solutions for the Matrix Differantial Equations - Gencoglu, M. Tuncay (Fırat University, 2015)
In this paper, the linear matrix differantial equations which is a special case of matrix differantial equations has been formulated by the consepts of of the matrix differantial equations and Kronecker products and investigated by the Kronecker products. The formulation of the matrix differantial equation obtained by use of the linear matrix equations and Kronecker products have been applied to the matrix differantial equations and some important results have been found. It is shown that in solutions of the equation and its reduced case have emerged the importance of generalized inverse matrix and matrix functions.

Bu çalışmada, matris diferansiyel denklemlerinin özel bir hali olan doğrusal matris diferansiyel denklemleri Kronecker çarpım ve matris diferansiyel denklemleri kavramalarıyla formüle edilmiş ve Kronecker çarpımlarla incelenmiştir. Kronecker çarpım ve doğrusal matris denklemler kullanılarak elde edilen doğrusal matris diferansiyel denklem formulasyonu matris diferansiyel denklemlere uygulanmış ve bazı önemli sonuçlar bulunmuştur. Denklemin ve onun indirgenmiş durumu genelleştirilmiş ters matris ve matris fonksiyonunun önemini ortay çıkarmıştır.
Matris Diferansiyel Denklemler için Kronecker Çözümler